Room temperature third-order nonlinear Hall effect in Weyl semimetal TaIrTe₄ - Wang, Cong (2022)
The second-order (2nd order) nonlinear Hall effect observed in time-reversal symmetric system has not only shown abundant physical contents, but also exhibited potential application prospect. Recently, a third-order (3rd order) nonlinear Hall effect has been observed in MoTe2 and WTe2. However, few-layer MoTe2 and WTe2 are usually unstable in air and the observed 3rd nonlinear Hall effect can be measured only at low temperature, which hinders its further investigations as well as potential applications. Thus, exploring new air-stable material systems with sizable 3rd nonlinear Hall effect at room temperature is an urgent task. Here, in a type-II Weyl semimetal TaIrTe4, we observed pronounced 3rd order nonlinear Hall effect, which can exist at room temperature and maintain stably for months. The 3rd order Hall effect is connected to the Berry-connection polarizability tensor instead of Berry curvature. The possible mechanisms for the observation of the 3rd order nonlinear Hall effect in TaIrTe4 at room temperature has been discussed. Our findings will open an avenue towards exploring room temperature nonlinear devices in new quantum materials.